Cristina Santos Pinheiro, Joaquim Pinheiro, Gabriel F. Silva & Rui Carlos Fonseca: Gynaikeia. Colectânea de Textos Antigos de Ginecologia, V. N. Famalição: Ed. Humus, 2022, 345 págs. ISBN: 978-989-755-802-3 - González Delgado, Ramiro (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2023)
Book review